'Addressing a Great Silence': Black Diggers and the Aboriginal Experience of War. (9th July 2015) - Syron, Liza-Mare
<x content-type="archive" xml:space="preserve">Abstract</x> In 2014 Indigenous theatre director Wesley Enoch announced in an interview that 'the aim of Indigenous theatre is to write into the public record neglected or forgotten stories'. He also spoke about the aims of a new Australian play, Black Diggers, as 'honouring and preserving' these stories. For Enoch, Black Diggers (re)addresses a great silence in Australia's history, that of the Aboriginal experience of war. Also in 2014, the memorial sculpture Yininmadyemi Thou Didst Let Fall, commissioned by the City of Sydney Council, aimed to place in memoriam the story of forgotten Aboriginal soldiers who served during international conflicts, notably the two world wars. Both Black Diggers and the Yininmadyemi memorial sculpture are counter-hegemonic artefacts and a powerful commentary of a time of pseudo-nationalist memorialization. Both challenge the validity of many of Australia's socio-political and historical accounts of war, including the frontier wars that took place between Aboriginal people and European settlers. Both unsettle Australia's fascination with a memorialized past constructed from a culture of silence and forgetfulness. Liza-Mare Syron is a descendant of the Birripi people of the mid-north coast of New South Wales in Australia. An actor, director, dramaturg, and founding member of Moogahlin Performing Arts, a Sydney-based Aboriginal company, she is currently the Indigenous Research Fellow at the Department of Media, Music, Communication, and Cultural Studies at Macquarie University, Sydney. She has published widely on actor training, indigenous theatre practice, inter-cultural performance, and theatre and community development.